2014
DOI: 10.1007/s11999-013-3030-7
|View full text |Cite
|
Sign up to set email alerts
|

What Are the Rates and Causes of Hospital Readmission After Total Knee Arthroplasty?

Abstract: Background Total knee arthroplasty (TKA) and related interventions such as revision TKA and the treatment of infected TKAs are commonly performed procedures. Hospital readmission rates are used to measure hospital performance, but risk factors (both medical and surgical) for readmission after TKA, revision TKA, and treatment for the infected TKA have not been well characterized. Questions/purposes We measured (1) the unplanned hospital readmission rate in primary TKA and revision TKA, including antibiotic-spac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
147
5
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 207 publications
(167 citation statements)
references
References 21 publications
13
147
5
2
Order By: Relevance
“…Identifying the mechanisms of failure in revision joint arthroplasties is critical to guiding efforts to improve clinical outcomes. Beyond clinical demands associated with revisions, the increasing economic burden of these procedures creates financial strains for surgeons, patients, and health systems [23,47,48]. These data may be important for healthcare systems to appropriately allocate resources in arthroplasty service lines: The revision burden for THA is greater than for TKA, but revision TKAs are increasing at a faster rate.…”
Section: Discussionmentioning
confidence: 99%
“…Identifying the mechanisms of failure in revision joint arthroplasties is critical to guiding efforts to improve clinical outcomes. Beyond clinical demands associated with revisions, the increasing economic burden of these procedures creates financial strains for surgeons, patients, and health systems [23,47,48]. These data may be important for healthcare systems to appropriately allocate resources in arthroplasty service lines: The revision burden for THA is greater than for TKA, but revision TKAs are increasing at a faster rate.…”
Section: Discussionmentioning
confidence: 99%
“…In studies that also used detailed medical record review, medical complications contributed to 18% of unplanned readmissions after spine fusion for adult spinal deformity and 25% of readmissions after TKA [20,21]. Jencks et al [8] also found multiple different causes of hospital readmission after major hip or knee surgery, but as a result of the use of administrative claims data, the authors did not delineate all causes of readmission.…”
Section: Discussionmentioning
confidence: 99%
“…Patients undergoing orthopaedic surgery often have multiple coexisting medical conditions (comorbidities) [13,21,24,28,39,45,58]. Preoperative risk assessment can help with decision-making and management strategies [11,37,50].…”
Section: Introductionmentioning
confidence: 99%